2014
DOI: 10.1186/1746-6148-10-52
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial activity, antioxidant activity and selectivity index of leaf extracts of thirteen South African tree species used in ethnoveterinary medicine to treat helminth infections

Abstract: BackgroundDiseases caused by bacteria remain a major challenge globally and particularly in sub-Saharan Africa. The plants used in this study have been used in South Africa to treat helminth infections in livestock and humans. In a previous study we found a correlation between antifungal and anthelmintic activity in some cases. In this study we examined other potential uses of these thirteen plant species by determining the antibacterial and antioxidant activity of the leaf acetone extracts.The antibacterial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 22 publications
3
50
1
Order By: Relevance
“…Intestinal parasitic infections are among the most common chronic human infections in developing countries, particularly in the tropical and subtropical regions. Parasitic infection may lead to the release of free radicals which may have severe consequences on cellular metabolism (Adamu et al, 2014). The major groups of parasites are geohelminths, schistosomes and protozoan; these are associated with malnutrition, iron deficiency, anaemia growth and cognitive development impairment which are caused by decreased appetite, nutrient loss, malabsorption and decreased nutrient utilization (WHO, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal parasitic infections are among the most common chronic human infections in developing countries, particularly in the tropical and subtropical regions. Parasitic infection may lead to the release of free radicals which may have severe consequences on cellular metabolism (Adamu et al, 2014). The major groups of parasites are geohelminths, schistosomes and protozoan; these are associated with malnutrition, iron deficiency, anaemia growth and cognitive development impairment which are caused by decreased appetite, nutrient loss, malabsorption and decreased nutrient utilization (WHO, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Though much inventory had been compiled on medicinal plants in Africa, further research is still necessary with regards to the treatment of helminthes in order to avert complications associated with the treatment of intestinal worms (Kona and Atindehou, 2008;Adamu et al, 2014). Intestinal parasitic infections are among the most common chronic human infections in developing countries, particularly in the tropical and subtropical regions.…”
Section: Introductionmentioning
confidence: 99%
“…Many plant species possessed antioxidant potency, for example, lignan glucosides of S. vanprukii displayed stronger antioxidant effect than ascorbic acid (Thongphasuk et al, 2004), and S. nux-vomica had SOD activity (Vijayakumar et al, 2009). In addition, S. henningsii (Oyedemi et al, 2010) and S. mitis (Adamu et al, 2014) were shown to exert antioxidant activity. Interestingly, only the ethyl acetate extracts (30 g/mL) of stem bark, twig and leaf of S. lucida showed selective anticancer activity against MOLT-3 cells with 70, 68 and 86% inhibition, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The local healers who are knowledgeable and experienced in traditional veterinary health care use the locally available plants (Balaji & Chakravarthi, 2010). There are studies on the ethnoveterinary plants and their bioactivity (Doss, Mubaracki, vijayasanthi, & venkataswamy, 2012, Kalayou et al, 2012, Adamu et al, 2014, but the medicinal value of the endophytic fungi associated with these plants is very scarce (Nath & Joshi, 2014). Realizing the importance of ethnoveterinary practices and dwindling population of ethnoveterinary plants, bioactivity efficacy of endophytic fungi associated with these plants was explored in the present study to assess the potential of using the fungi as nanofactories for animal healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Ethno veterinary medicine (EvM) is practiced for its efficacy, low cost, availability and ease of administration, in comparison to other alternatives (Adamu, Naidoo & Eloff, 2014;Lulekal, Asfaw, Kelbessa, & Damme, 2014;Yigezu, Haile, & Ayen, 2014). In the present study, ethnoveterinary plants, Garcinia xanthochymus H. and Polygonum chinense L. which are widely used by the local livestock farmers of Northeast India for curing diarrhea and dysentery in animals, were evaluated for their antimicrobial activity along with the associated fungi.…”
mentioning
confidence: 99%